2008
DOI: 10.2169/internalmedicine.47.0740
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of 852 Patients with Subacute Thyroiditis before Treatment

Abstract: Objective Subacute thyroiditis (SAT) is a transient inflammatory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
190
4
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(222 citation statements)
references
References 18 publications
12
190
4
16
Order By: Relevance
“…Nishihara et al previously examined the clinical characteristics of 852 untreated patients with SAT, and reported that 28.2% of the patients were febrile (body temperature ≧ 38°C in 19.2%), and that ≧ 60% had clinical symptoms and signs of thyrotoxicosis at the onset of the disease [12]. In our study, the mean body temperature was 37.0 ± 0.6°C (≧ 38°C in 19.2%), and symptoms of thyrotoxicosis were observed in 57.7% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nishihara et al previously examined the clinical characteristics of 852 untreated patients with SAT, and reported that 28.2% of the patients were febrile (body temperature ≧ 38°C in 19.2%), and that ≧ 60% had clinical symptoms and signs of thyrotoxicosis at the onset of the disease [12]. In our study, the mean body temperature was 37.0 ± 0.6°C (≧ 38°C in 19.2%), and symptoms of thyrotoxicosis were observed in 57.7% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, SAT may similarly manifest with increased body temperature, a significant elevation of ESR and CRP but rather no leukocytosis, firm and painful goiter, with pain of typical radiation. However, SAT is usually accompanied by thyroid dysfunction (11). CAT can be diagnosed at any thyroid functional state, but typically it is not characterized by painful thyroid enlargement and biochemical or clinical signs of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Disfunções de tireoide e paratireoide foram des critas na TA, sendo a elevação transitória de tiroxina, decorrente da liberação de estoques hormonais pelo processo de destruição folicular, algumas vezes acom panhada de sinais clínicos de tireotoxicose, a alteração mais frequentemente verificada (1,15).…”
Section: Discussionunclassified